Consumer‐driven nutrient dynamics in urban environments: the stoichiometry of human diets and waste management. Issue 7 (8th April 2015) - Cease, Arianne J.; Capps, Krista A.; Gates, Kiza K.; McCrackin, Michelle L.; Nidzgorski, Daniel A.
<x xml:space="preserve">Abstract</x> Studies in both terrestrial and aquatic ecosystems have documented the potential importance of consumers on ecosystem‐level nutrient dynamics. This is especially true when aggregations of organisms create biogeochemical hotspots through nutrient consumption, assimilation, and remineralization via excretion and egestion. Here, we focused on aggregations of humans in cities to examine how diet and waste management interact to drive nitrogen‐ (N) and phosphorus‐ (P) fluxes into nutrient pollution, inert forms, and nutrient recycling. We constructed six diet patterns (five US‐based and one developing nation) to examine N‐ and P‐consumption and excretion, and explored their implications for human health. Next, we constructed six waste‐management patterns (three US and three for developing nations) to model how decisions at household and city scales determine the eventual fates of N and P. When compared to the US Recommended Daily Intake, all US diet patterns exceeded N and P requirements. Other than the "enriched CO2 environment scenario" diet, the typical US omnivore had the greatest excess (37% N and 62% P). Notably, P from food additives could account for all of the excess P found in US omnivore and vegetarian diets. Across all waste‐management approaches, a greater proportion of P was stored or recycled (0 to > 100% more P than N) and a greater proportion of N was released as effluent (20 to > 100% more N than P) resulting in pollution enriched with N and a recycling stream enriched with P. In developing nations, 60% of N and 50% of P from excreta entered the environment as pollution because of a lack of sanitation infrastructure. Our study demonstrates a novel addition to modeling sustainable scenarios for urban N‐ and P‐budgets by linking human diets and waste management through socio‐ecological systems.